Passing Skills in Volleyball Games for Extracurricular Students at SMA Negeri 2 Gowa - Latuheru, Ricardo Valentino (Sains Global Institut, Indonesia, 2024)
The purpose of this study is to find out the passing skills of extracurricular students of SMA Negeri 2 Gowa. The research method used is quantitative descriptive. Data collection in this study was carried out by testing the upper test passing skills. The population in this study is extracurricular students of SMA Negeri 2 Gowa with a total of 20 students (Random Sampling). The data analysis technique used in this study is by way of passing a test. The data analysis technique used is descriptive analysis with percentages. Based on the results of the analysis of passing skills for extracurricular students of SMA Negeri 2 Gowa, the very good category is 0 students with a percentage of 0.00%, the good category is 7 students with a percentage of 35.00%, the medium category is 4 students with a percentage of 20.00%, the category is less than 4 students with a percentage of 20.00% and the category is less than 5 students with a percentage of 25.00%. It can be concluded that the passing skills of extracurricular students of SMA Negeri 2 Gowa are included in the Good category.